2022
DOI: 10.1007/s11368-022-03145-8
|View full text |Cite
|
Sign up to set email alerts
|

Kettle holes reflect the biogeochemical characteristics of their catchment area and the intensity of the element-specific input

Abstract: PurposeKettle holes are small inland water bodies known to be dominated by terrigenous material; however, the processes and structures that drive the enrichment and depletion of specific geochemical elements in the water column and kettle hole sediment remain unclear. We hypothesized that the mobile elements (Ca, Fe, K, P) behave different from each other in their transport, intermediate soil retention, and final accumulation in the kettle hole sediment. MethodsTopsoils from transects spanning topographic posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition, studies have found the majority of OC resides in the finer soil fractions (Yu et al 2019;De Mastro et al 2020). This finer fraction was present in both soil and sediment samples, however, runoff from eroding landscapes can be enriched in these finer, clay sized particles (Starr et al 2000;Nitzsche et al 2022) and could have affected the n-alkane distribution of streambed sediments relative to the source samples in this study (Laceby et al 2017). In future studies, analysing terrestrial source soils at different particle size fractions could help quantify any effects on n-alkane distributions due to this factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found the majority of OC resides in the finer soil fractions (Yu et al 2019;De Mastro et al 2020). This finer fraction was present in both soil and sediment samples, however, runoff from eroding landscapes can be enriched in these finer, clay sized particles (Starr et al 2000;Nitzsche et al 2022) and could have affected the n-alkane distribution of streambed sediments relative to the source samples in this study (Laceby et al 2017). In future studies, analysing terrestrial source soils at different particle size fractions could help quantify any effects on n-alkane distributions due to this factor.…”
Section: Discussionmentioning
confidence: 99%